Targeting acidic pre-metastatic niche in lungs by pH low insertion peptide and its utility for anti-metastatic therapy - Matsui, Toma; Toda, Yuki; Sato, Haruka; Itagaki, Rina; Konishi, Kazuya; Moshnikova, Anna; Andreev, Oleg A.; Hosogi, Shigekuni; Reshetnyak, Yana K.; Ashihara, Eishi (Frontiers in Oncology, 2023)
Dysregulated extracellular pH, the universal feature of tumor, works as an evolutional force to drive dissemination of tumor cells. It is well-established that tumor acidity is associated with tumor growth and metastasis. However, the pH of pre-metastatic niche remains unclear. We hypothesized that primary tumor cells remotely prime acidity in secondary organ to achieve metastatic colonization. Herein, we demonstrated that the pH responsive probe pH Low Insertion Peptide (pHLIP) was notably accumulated in pre-metastatic lungs of 4T1.2 breast tumor-bearing mice. The pHLIP-targeted lungs showed high amounts of lactate and overexpressed glycolysis-related proteins. Pharmacological inhibition of glycolysis suppressed the lung acidification induced by 4T1.2 cancer cell culture supernatant and delayed subsequent metastatic burden of disseminated tumor cells. In the acidic lungs, pHLIP was primarily localized in alveolar type 2 cells which strongly expressed glycolysis-related proteins. 4T1.2-derived extracellular vesicles expressed some of the glycolysis-related proteins, and their administration increased pHLIP accumulation and glycolytic enhancement in lungs. pHLIP-conjugated dexamethasone effectively attenuated lung metastatic burden by disrupting pro-inflammatory response in the acidic lungs. From these results, targeting the metastasis-supporting microenvironment by pHLIP technology creates possibility to identify pre-metastatic organ and prevent metastatic recurrence.